Sistem Informasi Pengajuan Judul Skripsi Fakultas Ilmu Komputer Universitas Panca Budi Menggunakan Bahasa Pemrograman Berbasis Web - Fitri Aini Nasution (Jurnal Informatika, 2022)
Universitas pembangunan pancabudi in submitting thesis titles and approving thesis titles still in a simple way, remembering that now the technology is already sophisticated, so the writer makes an information system for submitting titles online, namely by way of students submitting thesis titles and head of study program approving thesis titles online, after that the head of study program enters a supervisor who will guide students but, students can print a certificate form as proof that the title of the thesis has been approved, with this system is expected to facilitate students in the submission of thesis title. With this new system, students and related sections will be easier to submit and process data that includes all thesis title submission data so that the title submission process can run effectively. In addition, students will be easier to get the information needed to facilitate students in the process of submitting thesis titles and get the signature of the head of the study program system as well as to get the signature of the supervisor so that students do not need to come to the campus to see the results of the submission of thesis titles this application is designed by using PHP and MYSQL as the database with a web-based programming language.